A Significant Source for the Madeleine and Other Major Episodes in Combray: Proust's Intertextual Use of Pierre Loti's My Brother Yves - Richard M. Berrong (Studies in 20th & 21st Century Literature, 2014)
The most famous passage in Marcel Proust’s In Search of Lost Time, and one of the most famous passages in Western literature, is the moment when the narrator sips tea while eating a shell-shaped pastry called a madeleine and suddenly recalls very vividly an apparently long-forgotten scene from his childhood. From this episode Proust developed his theories about involuntary memory and its important role in our emotional welfare. Proust was an avid reader of the French novelist Pierre Loti when he was young. Contemporary accounts show that he was able to recite whole passages from Loti’s work in public from memory. This article demonstrates the extent to which Proust made intertextual use of scenes from Loti’s novel My Brother Yves in constructing the madeleine and other famous passages in Combray, the first section of In Search of Lost Time. It does not attempt to question the originality of Proust’s work. Rather, building on previous studies of intertextuality in Proust, it seeks to show how the author went about creating his work and dialoguing with at least some of his potential contemporary readers.
Keywords: Marcel Proust; Pierre Loti; My Brother Yves; intertextuality